(untitled) (Revista de Ciência Veterinária e Saúde Pública, 2020)
The COVID-19 caused by the coronavirus 2 severe acute respiratory syndrome (SARS-CoV-2), was first reported in Wuhan, China, starting an outbreak that affected countries around the whole world. The disease leads to simple clinical signs, such as colds common to more serious conditions as pneumonia and severe respiratory insufficiency. It is assumed that the agent was originated from bats in China, considering its as natural reservoirs, however, this relationship is still being investigated, as well as the possible intermediate hosts. Little is known about the relationship of animals with the disease epidemiological cycle, however, until now, the human transmission to companion animals and vice versa, is not yet evidenced. Nevertheless, some care must be considered if the tutors are infected by the disease.